Development of a mechanical system design workbench for use in a virtual environment - Fok, Sai Cheong. (2008)
This report presents the project work done on the development of a mechanical system design workbench for use in a virtual environment. The main objectives are: (i) To develop facilities for virtual prototyping simulation for design of mechanical systems. This includes facilities for real-time machinehuman-in-the-loop simulation, dynamic performance simulation, design sensitivity analysis, design optimisation and human factors study. (ii) To develop a methodology for the incorporation of modeling and simulation tools from the field of multibody dynamics into a virtual simulator, so that its repertoire may be expanded to include articulated systems free to move in space. (iii) To develop an intelligent workbench for the collaborative design and virtual prototyping of hydraulic systems